2023
DOI: 10.1039/d3cp04297a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks (MOFs) for energy production and gaseous fuel and electrochemical energy storage applications

Mariyappan Shanmugam,
Nithish Agamendran,
Karthikeyan Sekar
et al.

Abstract: The increasing energy demands of human society and industrial sectors have inspired to search for alternative energy sources that are renewable and sustainable, and also push forward for developing clean...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 214 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…52−54 This parameter makes them exceptionally adept at gas storage, 55 catalytic processes, 56 and adsorption, 57 rendering MOFs indispensable in numerous domains. 58 The intricate framework with readily accessible internal porosity makes MOF surpass conventional coordination complexes. These pores favor the expansive surface area and enable facile accommodation of guest molecules for numerous applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52−54 This parameter makes them exceptionally adept at gas storage, 55 catalytic processes, 56 and adsorption, 57 rendering MOFs indispensable in numerous domains. 58 The intricate framework with readily accessible internal porosity makes MOF surpass conventional coordination complexes. These pores favor the expansive surface area and enable facile accommodation of guest molecules for numerous applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The multifaceted utility and tunability for various applications have garnered considerable attention for MOFs. The pivotal characteristic of MOFs is their exceptionally high surface area. By orders of magnitude, some MOFs can surpass traditional porous materials by exhibiting very high surface area. This parameter makes them exceptionally adept at gas storage, catalytic processes, and adsorption, rendering MOFs indispensable in numerous domains . The intricate framework with readily accessible internal porosity makes MOF surpass conventional coordination complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal-organic frameworks (MOF), emerging metal ions, and organic ligand material with high surface area, crystalline structure, bandgap tunability, and charge transport have created widespread attention among researchers around the world. The high porosity of the MOFs, which promotes the diffusion rate of the products and reactants, contributes to these attractive properties [13,14]. Research has shown that MOFs can act as excellent semiconductors, and their bandgap tunability property makes them ideal candidates for photocatalysis [15].…”
Section: Introductionmentioning
confidence: 99%